The Moderating Role of Employee Empowerment and Distributive Justice in Transformational Leadership with Its Impact on Organizational Commitment in Islamic Banks at Pakistan - Maaz Ud Din; Faisal Khan; Ana Kadarningsih; Amjad Ali; Sih Darmi Astuti (Perisai : Islamic Banking and Finance Journal, 2019)
The basic of the current studywas to discover the influence of transformational leadership on organizational commitment,distributive justice, and employee empowerment as moderate variables in the Islamic banking company of DistrictSwat, KP-Pakistan.Adopted questionnaires were used to have five pointsLikert scalesand containing 24 items. 18 samples were taken with Random Sampling Techniquesfrom the Islamic bank's sector.A total of 305 questionnaires were distributedamong employees and the feedback rate was 80 % which 245questionnaires received.Data analysis used multiple linear regression. The study found thatorganizational commitment is positively and significantly affect empowerment. Distributive justice has a positive influence on organization commitment but not significant. There was also found that the leadership of transformational influences organization commitment positively and significantly.The variance of transformational leadership and organizational commitments were 16% which indicates a weaksignificant influence.